EFEKTIVITAS PELAKSANAAN PROGRAM KESEJAHTERAAN SOSIAL ANAK JALANAN OLEH YAKMI KELURAHAN AUR KECAMATAN MEDAN MAIMUN - Fadlika Sya’bana (Welfare StatE, 2013)
On August 30, 2012 in the city of Medan, North Sumatra, the government launched the Social Welfare Program. This program was established on the basis of the increasing number of street children in Indonesia. The goal is to realize the fulfillment of children's rights and protection of children from neglect, violence, exploitation, and discrimination so that growth and development, child survival and participation can be realized. This study uses descriptive type because this study describe the object or subject of research in the form of data that already exists and aims to describe the characteristics of the object or subject in detail. The research was conducted in Medan District Maimoon Aur village by the number of respondents 20 special on street children ministry activities in 2012. Results of research conducted and data analysis has been carried out that the implementation of the program of activities of street children's ministry by looking at indicators of effectiveness, namely reaction, learning, behavior, and the impact of the implementation. Where the child is not difficult to obtain the funds, have an equal opportunity for each individual, providing for changes in their lives especially children's basic needs and can show good results under 1 year. From these results it can be concluded that the effective implementation of these activities. Keywords: Effectiveness, Social Welfare of Program.